Kompetencje legislacyjne konferencji episkopatu w sprawach małżeńskich w Kodeksie prawa kanonicznego z 1983 roku - Adamczyk, Jerzy (Ius Matrimoniale, 2019)
The aim of the article is to discuss the Bishop’s Conference’s publication of new standards concerning the issues of marriage, which complementthe Code of Canon Law. The first part of the article focuses on the legislative power of the Episcopal Conference. The second part concerns the problem of the legislative competences of the Episcopal Conference concerning the issues of marriage as included in the Code of Canon Law of 1983. The third and the fourth parts reveal the obligatory and optional legislative competences of the Episcopal Conference in the sphere of marriage as presented in the CCL. The article ends with conclusions and bibliography.